Epigenetic Cancer Prevention Mechanisms in Skin Cancer - Saha, Kamalika (Springer US, 2013)
Epigenetics is an important emerging area for study of mechanisms of cancer prevention. In recent years, it has been realized that cancer prevention agents, derived from natural dietary sources, impact cancer cell survival by modulating epigenetic processes. In the present manuscript, we review key epigenetic regulatory mechanisms and examine the impact of sulforaphane and green tea polyphenols on these processes. We also discuss available information on the epigenetics in the context of skin cancer. These studies indicate that diet-derived chemopreventive agents modulate DNA methylation status and histone modification via multiple processes and point to additional areas for study of epigenetic mechanisms in skin cancer.